Preactivation of neutrophils and systemic oxidative stress in dogs with hyperleptinemia - Bosco, A. M. [UNESP]; Almeida, B. F.M. [UNESP]; Valadares, T. C. [UNESP]; Baptistiolli, L. [UNESP]; Hoffmann, D. J. [UNESP]; Pereira, A. A.F. [UNESP]; Lima, V. M.F. [UNESP]; Ciarlini, P. C. [UNESP] (Elsevier, 2018)
High occurrence of obesity currently constitutes the main nutritional disease of the canine species. There is evidence that leptin increases during obesity in dogs. Hyperleptinemia is associated with increased neutrophil oxidative metabolism in obese humans and contributes to oxidative stress. However, in obese dogs, the probable relationship between this condition and the activation of the oxidative metabolism of neutrophils has yet to be established. Thus, we investigated the hypothesis that neutrophil activation and systemic oxidative stress occur in dogs with hyperleptinemia. A control group of 24 healthy dogs with a body condition score (BCS) of 4–5, an overweight group of 25 dogs with a BCS of 6–7, and 27 obese dogs with a BCS of 8–9, were composed. Two subgroups were formed composed of dogs with and without hyperleptinemia, grouped according to the 95% confidence interval obtained for plasma leptin values of the control group. Changes in obesity markers (body condition score, adiponectin and plasma leptin) and plasma oxidative stress (lipid peroxidation, total antioxidant and oxidant capacities and oxidative stress index) were measured in all the dogs selected. Neutrophil oxidative metabolism was evaluated in flow cytometry by superoxide production with the probe hydroethidine and by hydrogen peroxide production with the probe 2′,7′-dichlorofluorescein diacetate, with or without phorbol myristate acetate (PMA) stimulation. Apoptosis and neutrophil viability were quantified in a capillary flow cytometer using Annexin V–PE, with or without camptothecin apoptosis inducing effect. Obese dogs presented higher systemic oxidative stress, hyperleptinemia and preactivated neutrophils with accelerated apoptosis. Dogs with hyperleptinemia and obese dogs presented higher neutrophil superoxide production under PMA stimulation and the presence of systemic oxidative stress compared with control. To our knowledge, this is probably the first evidence that preactivation of the oxidative metabolism of circulating neutrophils occurs in dogs with hyperleptinemia, a condition that can induce systemic oxidative stress in the canine species.
Keywords: Apoptosis; Leptin; Obesity; Polymorphonuclear; Superoxide